Virulence profile of pathogenic yeasts from snakes: Alternative ways for antifungal strategies - Iniobong Chukwuebuka I. Ugochukwu; Jairo Alfonso Mendoza-Roldan; Mara Miglianti; Natalizia Palazzo; Amienwanlen Eugene Odigie; Domenico Otranto; Claudia Cafarchia (PLoS ONE, 2025)
Reptiles may act as reservoirs or spreaders of potential pathogenic microorganisms including Candida yeasts. While the epidemiology of yeast species has been thoroughly studied, the virulence profile of isolated species is not well investigated. Therefore, this study aimed to assess the haemolytic, phospholipase, lipase activities and biofilm formation of yeasts isolated from the cloacal swabs of venomous snakes from Marrakech, Morocco (Group I, n = 40) and from non-venomous snakes from Cocullo, Italy (Group II, n = 32). All the isolated yeasts from Group 1 showed low production of lipase (Lz ≥  0.90) and haemolysin (Hz ≥ 0.90), and only 35% of them were low phospholipase (Pz) producers (Pz > 0.90). In contrast, all the yeasts from Group 2 produced enzymes and more than 62% produced high amounts of enzymes (Pz ≤  0.64; Lz ≤  0.69; Hz ≤ 0.69). Data show that yeasts from snakes were able to produce virulence factors, which vary according to the yeast species and the hosts or their origin, thus suggesting the potential role of snakes in harboring and spreading pathogenic yeasts in the environment. Since the virulence profile was lower in venomous snakes than that in non-venomous ones, we discussed that it may be affected by the venom composition. This will pave the way for fungal infection control, alternative to antifungal drugs in order to overcome resistance phenomena.